2005
DOI: 10.1111/j.1463-1326.2005.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: effect of hormone‐replacement therapy on components of the metabolic syndrome in postmenopausal women

Abstract: HRT reduces abdominal obesity, insulin resistance, new-onset diabetes, lipids, blood pressure, adhesion molecules and procoagulant factors in women without diabetes and reduced insulin resistance and fasting glucose in women with diabetes. Oral agents adversely affected CRP and protein S, while transdermal agents had no effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
297
1
17

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 508 publications
(353 citation statements)
references
References 155 publications
19
297
1
17
Order By: Relevance
“…Confirming our results of a difference between the oral and cutaneous route of oestrogen administration on the risk of new-onset diabetes, a recent meta-analysis found a larger protective effect on components of metabolic syndrome with oral MHT than with transdermal MHT [15], possibly because of a stronger effect of oral than transdermal oestradiol on peripheral vascular reactivity [34]. Few studies have examined associations with a given progestagen according to the route of administration of the associated oestrogen.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Confirming our results of a difference between the oral and cutaneous route of oestrogen administration on the risk of new-onset diabetes, a recent meta-analysis found a larger protective effect on components of metabolic syndrome with oral MHT than with transdermal MHT [15], possibly because of a stronger effect of oral than transdermal oestradiol on peripheral vascular reactivity [34]. Few studies have examined associations with a given progestagen according to the route of administration of the associated oestrogen.…”
Section: Discussionsupporting
confidence: 76%
“…A decreased peripheral blood flow may limit insulin delivery and promote insulin resistance. Results of the WHI trial suggested that a decrease in insulin resistance, induced by the MHT, may have been responsible for the lower incidence of diabetes observed in the women who received the active treatment [13,14]; these results were confirmed in a meta-analysis [15]. As in a recent study [36], the relationship was no longer significant after discontinuation of MHT use, when the model was adjusted for BMI during follow-up.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations